Why peacekeeping fails - a comparative assessment of Angola and Mozambique - Jett, Dennis C (My University, 2014)
This thesis examines why some peacekeeping operations (PKOs) fail, principally by comparing the unsuccessful attempt at peacekeeping in Angola to the successful effort in Mozambique. It tests the hypothesis that, while the factors that have led to failures in the past can be identified and the elements of success predicted, the likelihood of increasing the probability of success is made difficult by the way PKOs are initiated and conducted, by the nature of the UN as an organization and by other factors the UN can influence, but not control. In examining the above hypothesis, a brief review of the history of peacekeeping is provided. The evolution in the number, size, scope and cost of such operations is described, as well as why peacekeeping has become more necessary, more possible and more desired. The thesis explains why PKOs have become increasingly complex and, as a result, their chances for success have diminished. It also shows how this has led to peacekeeping falling into relative disuse, The thesis looks at a wide range of PKOs and analyzes two of them in depth PKOs - UNAVEM II in Angola and ONUMOZ in Mozambique - during the three phases which every PKO goes through: the period leading up to dispatching the peacekeepers, during their deployment, and after they have departed. While Angola and Mozambique have similar histories, it is commonly believed that the outcome of their respective PKOs could hardly have been more different. The thesis considers whether the contrast between the two outcomes may not be as stark as this conventional wisdom suggests. Finally, the thesis attempts to draw conclusions about ways in which future PKOs could be conducted in order to improve the chances for success. It also considers why these changes are easier to enumerate than to adopt and implement. Research for the thesis was conducted through semistructured interviews of policy makers, analysts and participants selected because of their knowledge of peacekeeping operations. The extensive academic literature on peacekeeping, newspaper and magazine articles, UN and other official documents, speeches, congressional testimony and unpublished papers by participants in PKOs were also extensively utilized. The thesis was also based, in part, on first-hand experience, as the candidate has observed peacekeeping efforts in Mozambique, Angola, Israel, Liberia and Peru.
Thesis (Ph.D.)--University of the Witwatersrand, Faculty of International Relations, 1998.